Pupuk Organik Berkemasan untuk Program Rumah Pupuk Desa Solusi Efektif untuk Pertanian Lokal - Nareswari, Aptika Hana Prastiwi (Jurnal Abdi Masyarakat, 2025)
The community service in Purwokerto Village, Kediri Regency, aims to optimize cow dung waste from the largest livestock cooperative into high-quality organic fertilizer to support local agriculture. The program involves collecting cow dung and formulating various organic fertilizers, such as cocopeat, husk-based, liquid, and decomposers. Members of the Sumber Mulyo Kerto Tani Makmur Gapoktan actively participate in the production process. The organic fertilizers are then commercialized. The project has been positively received, particularly for its solid husk and cocopeat fertilizers, which meet standards with a ppm level above 2000, improving soil properties. This initiative provides an alternative fertilizer source for farmers, contributing to their welfare and advancing agriculture in Purwokerto Village